1987
DOI: 10.1042/bj2410693
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a phosphoprotein in the nuclear matrix by monoclonal antibodies

Abstract: Previous work in this laboratory has established that a rat liver nuclear phosphoprotein (B2:Mr 68,000, pI 6.5-8.2) is associated with actively transcribed nucleosomes, as demonstrated by its preferential release after mild treatment with micrococcal nuclease. In the present report we provide further immunological evidence ('Western Blot' analysis, solid-phase radioimmunoassay and indirect immunofluorescence) that in addition establishes the presence of this phosphoprotein in the nuclear-matrix protein fractio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

1988
1988
1997
1997

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Halikowski and Liew (51) have also identified a presumptive chromatin protein(s) termed B2 that migrated in the same general position as this basic cluster. B2, which is also a highly phosphorylated protein, was shown to be also associated with the nuclear matrix (52).…”
Section: Discussionmentioning
confidence: 99%
“…Halikowski and Liew (51) have also identified a presumptive chromatin protein(s) termed B2 that migrated in the same general position as this basic cluster. B2, which is also a highly phosphorylated protein, was shown to be also associated with the nuclear matrix (52).…”
Section: Discussionmentioning
confidence: 99%
“…Monoclonal antibodies have been produced to this protein and have been used in Western blot analyses. We have also shown that the antigen is present in the nuclear matrix [12]. This nuclear antigen has a molucular weight of 68 kDa and exhibits heterogeneity due to a p1 ranging from pH 6.5 to 8.2.…”
Section: Discussionmentioning
confidence: 86%
“…Western blotting conditions were also described previously [8,15] and utilized '251-protein A and autoradiographic detection system. …”
Section: Methodsmentioning
confidence: 99%
“…Characterization of monoclonal antibodies and the radioimmunoassay were as described previously [7]. Western blotting conditions were also described previously [8,15] and utilized '251-protein A and autoradiographic detection system.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation